On the Dynamics of Conspicuity. (September 2019) - Hancock, P. A.
Objective: To examine the influences of dynamic conspicuity on object recognition and to evaluate the real-world implications of these processes. Background: Conspicuity is the major influence on persons' abilities to recognize the presence of entities within their environment. Shortfalls in sensory and cognitive conspicuity are implicated in many, if not most, real-world systemic failures. Method: The present observations derive from an overview of relevant empirical research allied to a synthetic integration. From these foundations, I articulate a proposed taxonomy through which to parse the essential dimensions of conspicuity. Results: The taxonomy features three axes related to (a) modality (e.g., visual vs. auditory, etc.), (b) processing directionality (e.g., top-down vs. bottom-up information flow), and finally (c) temporality (i.e., the differences between static vs. dynamic presentations). Conclusion: Existing conspicuity studies have primarily featured static, sensory comparisons. Exploration of the other quadrants of the proposed taxonomy can serve to frame future conspicuity research. This taxonomic description also provides the basis from which to understand failure etiology in a wide spectrum of human–machine systems. Application: Improvements in the understanding of conspicuity can help in all domains of HF/E and can serve to reduce failure in a wide variety of operational contexts.